ARAFAT NUR'S CRITICISM OF SYMBOLIC OR SUBJECT ORDERS IN NOVEL BURUNG TERBANG DI KELAM MALAM - Merdika, Fitri Tiara (University of Brawijaya, 2021)
In the creation of literary works, either consciously or unconsciously the author will always insert his ideology. The insertion of the ideology can be seen from the criticisms delivered by the author. Literary works are a medium for the author to convey a critique of the reality that occurs, be it religious, social, cultural, political and other criticisms. But that becomes interesting when the author tries to open up an unconscious reality, opening up the decay of a system of power that will eventually become cynicism and submit to an ideological order. In this study, Arafat Nur's novel Burung Terbang di Kelam Malam was chosen to prove this ideological fantasy. The problem contained in this study is (1) What is the symbolic order of acehnese people in the novel Burung Terbang di Kelam Malam? (2) What is Arafat Nur's criticism of the subject (Acehnese) in the novel Burung Terbang di Kelam Malam? To answer that question, the theory used was an authentic subject and ideological fantasy introduced by Slavoj Zizek and analyzed with descriptive analytical methodology.The results of this study prove that, firstly, the symbolic order (Islamic Sharia as the identity of Aceh) failed to form a radical subject. Although the subject has relinquished the symbolic order that shackled him all along, he remains returning to the new symbolic order. The subjects who are still in power of the Big Other will never escape from the order that subjected them. The subject will not be able to reach the Real, because they cannot discuss it so the subject desires to fulfill Che Vuoi's call?, unconsciously the subject commits ideological fantasies. Second, the subject of fantasizing the ideology of Islamism (Islamic sharia) that desires the achievement of spirituality instead leads it to capitalism. Not just the subject (the character in the novel). Arafat Nur as an author was also caught up in capitalism so his attempts to go radical ended in failure.Â Keywords: Ideological fantasy, subjectivity, symbolic order, Burung Terbang di Kelam Malam, Arafat Nur